Digital identity management - Laurent, Maryline; Bouzefrane, Samia (ISTE Press Elsevier, 2015)
This book addresses our current progress and viewpoints on digital identity management in different fields (social networks, cloud computing, Internet of Things (IoT), with input from experts in computer science, law, economics and sociology.